Tolerance Education in Muslim Minority Educational Institutions in Cambodia, Thailand, and Indonesia - Kosim, Muhammad; Martin Kustati; Hosen Mohamad Farid; Mahamadaree Waeno; Wahida Raihan Sirait; Suryadi Fajri (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This study aims to analyze tolerance education policies and their integration into the curriculum of Islamic educational institutions in Muslim-minority areas: Phnom Penh (Cambodia), Hat Yai (Thailand), and Mentawai (Indonesia). Highlighting good practices in tolerance education is essential to strengthen Islamic education and counteract negative stigmas of Muslim minorities as intolerant or extremist. Design/methods/approach – Employing a mixed-methods approach with a cross-sectional design, this research prioritizes qualitative methods supported by quantitative data. Data were collected through in-depth interviews, Focus Group Discussions (FGDs), documentation, and questionnaires. Findings – Tolerance education is implemented contextually, shaped by each country’s socio-political environment. In Cambodia, it is promoted through harmonious intergroup relations, a flexible curriculum, and state support, particularly from the monarchy and the Mufti’s autonomy in developing Islamic schools. In Thailand, private Islamic schools implement tolerance by aligning with the royal education framework, encouraging interfaith student interaction, and emphasizing Islamic teachings as rahmatan lil 'alamin. In Indonesia, state madrasas incorporate tolerance education systematically through national programs like Religious Moderation. Research implications/limitations – The findings underscore the importance of context-responsive educational policies to foster social harmony and prevent early signs of intolerance. This research is limited to specific regions but offers transferable insights. Originality/value – This study contributes original insights into how tolerance education can be effectively embedded within Islamic education curricula in minority Muslim contexts by adapting to local policies and cultural dynamics, fostering inclusive Islamic communities based on principles of mercy and coexistence.